Advances in the management of paediatric Cushing's disease. - Savage, M; Chan, L; Afshar, F; Plowman, P; Grossman, AB; Storr, H (2008)
Cushing's disease (CD) is rare in the paediatric age range, but may present a difficult therapeutic challenge. Most paediatric endocrinologists have limited experience managing children or adolescents with CD and thus benefit from close consultation with adult colleagues. Prior to definitive treatment, a diagnostic protocol for investigation is required which broadly follows the model for adult patients. Treatment strategies for CD are described and critically appraised. The management of paediatric CD patients after cure also presents challenges for optimizing growth, bone health, reproduction and body composition from childhood into and during adult life.